KOORDINASI PEMERINTAHAN DALAM PENATAAN BATAS DESA DI KABUPATEN BANGKA TENGAH PROVINSI KEPULAUAN BANGKA BELITUNG - Dewi Dewi; Fernandes Simangunsong (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Thefocus of this research is to explore, collect, manage and analyze government coordination in delineating village boundaries in Central Bangka Regency, Bangka Belitung Islands Province. Factors that influence and determine the concept of government coordination in structuring village boundaries in Central Bangka Regency, Bangka Belitung Islands Province to make it better. The research uses the theory by Erliana Hasan and Eva Eviany regarding government coordination and supporting and inhibiting factors. Research using descriptive qualitative method. In collecting data the researcher conducted interviews, documentation, observation and data triangulation regarding government coordination in delineating village boundaries in Central Bangka Regency, Bangka Belitung Islands Province. The results showed that government coordination in delineating village boundaries in Central Bangka Regency, Bangka Belitung Islands Province, still had problems. There were several villages in Central Bangka Regency that had not yet received boundary determination and confirmation. Supporting and inhibiting factors that influence government coordination activities in village boundary arrangement so that they run well based on the theory of Erliana Hasan and Eva Eviany include: Availability and easy access to information, communication and technology, There is awareness and understanding of the importance of coordination, Availability of containers that accommodate aspirations and desires, Existence agreement and commitment to communicate with each other in a transparent and scheduled manner, There is an MOU for the establishment of an agreement by each coordinating party, There are incentives for coordination in communication, Feedback as feedback for the next coordination process.